Radiative decay Y (4260) - X (3872)+ү involving hadronic molecular and charmonium components; Physical Review D; Vol. 90, iss. 7 - Yubing Dong,; Faessler A.; Gutsche Th.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2014, 2014)
Title screen